Food security and the cultural heritage missing link - Britwum, Kofi; Demont, Matty (Elsevier, 2022)
Though enormous strides have been achieved in recent decades towards reducing food insecurity in the Global South, continued efforts are imperative in light of rapidly expanding populations and threats posed by climate change. A relatively unexplored area in this arena is the nexus between cultural heritage and food security. Cultural heritage embodies indigenous culture, values, and traditions inherited from previous generations. We focus on rice and identify five pathways through which cultural heritage affects food security. Although policy makers face the complex task of balancing trade-offs between preserving cultural heritage and productivity, they can harness cultural heritage to enhance food security by supporting (i) preservation of genetic resources, (ii) valorization, (iii) traditional food processing, (iv) preference matching, and (v) agritourism.